A survey of Bicol music in Camarines Sur - Calisura, Paterno Abante (s.n.], 1993)
This research is focused only on six musically active communities of Camarines Sur. I conducted fieldwork in the month of November to February 1993 in the municipalities of Calabanga, Baao, Bombon, Canaman, Nueva Caceresa (Naga) and small town of Quipayo. (See map) In the book 400th years of christianization of Quipayo, these areas were mentioned as part of early Spanish missions, Quipayo being the earliest mission. Quipayo came from the word Qui and "Payo" which means the head. So in this place, Hispanic-Folk music then is plentiful which comprises half our collected materials.